How are Tongan Children Developing? Results from the Second National Census and Policy Recommendations for Better Child Development in Tonga - Brinkman, Sally; Sincovich, Alanna; Vu, Binh Thanh (World Bank, Washington, DC, 2019)
This policy brief presents findings from the second national census of children’s early development in Tonga; the Tongan early Human Capability Index. First conducted in 2014 and then again in 2017, results provide a snapshot of the current status of early childhood development in Tonga, demonstrate how children’s development has changed over time, highlight factors that are playing an important role in influencing children’s outcomes across the country, and provide policy recommendations for ways forward to provide all Tongan children with the opportunity to reach their developmental potential.